Standardisation in international franchising. - Koh, Daphne Mui Kiang. (2008)
The project examines the extent of standardisation using a highly standardised market entry, franchising. It investigates the impact of market considerations,namely target market, competition and environmental factors have on the level of standardisation of the marketing mix and its components.